2020
DOI: 10.1155/2020/8888677
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Nomogram for Predicting Cancer-Specific and Overall Survival among Patients with Medullary Thyroid Cancer

Abstract: Background. Medullary thyroid carcinoma (MTC) accounts for 1%–2% of thyroid cancer in the United States based on the latest Surveillance, Epidemiology, and End Results (SEER) data, and this study aimed to construct a comprehensive predictive nomogram based on various clinical variables in MTC patients who underwent total thyroidectomy and neck lymph nodes dissection. Methods. Data regarding 1,237 MTC patients who underwent total thyroidectomy and neck lymph nodes dissection from 2004 to 2015 were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Rozenblat et al 7 performed a retrospective multicenter study and revealed that LNR was an independent factor for DFS. Chen et al 29 used the SEER database to study 1237 patients. They found that LNR was an independent predictor of survival in MTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rozenblat et al 7 performed a retrospective multicenter study and revealed that LNR was an independent factor for DFS. Chen et al 29 used the SEER database to study 1237 patients. They found that LNR was an independent predictor of survival in MTC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Third, the parameters involved in the nomogram are easy to obtain and evaluate, which means that there is no cost burden associated with complex tests in clinical use. 43 Fourth, visual nomogram can enhance patients’ understanding, help doctors and patients communicate from a medical perspective, and further promote cooperation between patients and doctors, so as to achieve better treatment effects. 44 Additionally, the results of this study are conducive to the timely detection of patients with low overall survival, but it is still worth considering whether the results of the nomogram score can be used as the basis for intervention to improve the overall survival of ALM patients.…”
Section: Discussionmentioning
confidence: 99%
“…A binomial logistic-regression model was built using the variables significantly associated with TH replacement, and visualized as a nomogram for predicting the probability of TH replacement after surgery. Multiple previous studies have proved that the nomogram has better predictive performance [21][22][23]. To our knowledge, this is the first report of a nomogram for predicting benign thyroid disease.…”
Section: Discussionmentioning
confidence: 66%